Germ-line transmission and developmental regulation of a 150-kb yeast artificial chromosome containing the human beta-globin locus in transgenic mice. - Gaensler, K M (1993)
Sequential expression of the genes of the human beta-globin locus requires the formation of an erythroid-specific chromatin domain spanning > 200 kb. Regulation of this gene family involves both local interactions with proximal cis-acting sequences and long-range interactions with control elements upstream of the locus. To make it possible to analyze the interactions of cis-acting sequences of the human beta-globin locus in their normal spatial and sequence context, we characterized two yeast artificial chromosomes (YACs) 150 and 230 kb in size, containing the entire beta-globin locus. We have now successfully integrated the 150-kb YAC into the germ line of transgenic mice as a single unrearranged fragment that includes the locus control region, structural genes, and 30 kb of 3' flanking sequences present in the native locus. Expression of the transgenic human beta-globin locus is tissue- and developmental stage-specific and closely follows the pattern of expression of the endogenous mouse beta-globin locus. By using homology-directed recombination in yeast and methods for the purification and transfer of YACs into transgenic mice, it will now be feasible to study the physiological role of cis-acting sequences in specifying an erythroid-specific chromatin domain and directing expression of beta-globin genes during ontogeny.